(untitled) (Quaestiones Disputatae: temas en debate, 2022)
This article analyzes the training of judges and magistrates in Colombia, in order to configure a research area to investigate the culture of judicial initial training. The study is based on a descriptive-analytical model based on the Problem-Based Research (IBP) as a methodological proposal. In the first step, it identifies a problematic axis around initial judicial training; then it develops the problem, configured from the culture of initial judicial training, and ends with the approach of a specific problem: the conception and application of a pedagogical model in judicial initial training (ABP) through the virtual modality. It was found that the response to the most appropriate pedagogical and didactic criteria for initial judicial training in Colombia is an aspect of knowledge that requires further development depending on the characteristics of the socio-educational context; the profile of the contemporary judge and the use of Information and Communication Technologies (ICT).It is concluded that it is necessary to strengthen the processes of adaptation to change in the “culture” of judicial initial training, with a balance between theory and practice, and the consolidation of a guiding pedagogical model based on the PBL approach.